Forelimb proportions and fossorial adaptations in the scratch-digging rodent Ctenomys (Caviomorpha) - Elissamburu, Andrea (2011)
Members of the genus Ctenomys (tuco-tuco; Rodentia: Caviomorpha: Octodontidae) are considered scratch diggers. We compared the forelimbs of adult C. azarae with those of 13 species within other genera of caviomorph rodents to identify morphofunctional variation in osseous elements related to fossorial habits. Eight measurements of the humerus and ulna were used to construct five functional indices that were subjected to principal components analysis and simple comparisons among means. Ctenomys has a general morphology similar to that of terrestrial caviomorph rodents but exhibits some features that reflect its specialized fossorial condition, such as its comparatively large epicondyles. These features indicate greater muscular development and capacity for force production in the pronators and supinators of the forelimb and manus and flexors of the manus. The deltoid complex is well developed, indicating a large moment arm for the deltoid and latissimus dorsi muscles, which increases the capacity for force production on humeral flexion. Humeral indices are the best for differentiating fossorial forms from diggers, occasional diggers, generalized, and cursorial forms. Limb bone segments are used differently by highly fossorial and scratch-digging forms.